Nipple-sparing Mastectomy with Immediate Implant-based Reconstruction for Patients with Pure Ductal Carcinoma in Situ - Frasson,Antônio Luiz (2022)
Abstract Objective The presence of an extensive intraductal component is associated to an increasing risk of relapse in the nipple-areola complex. The aim of the present study was to evaluate the outcomes of patients diagnosed with ductal carcinoma in situ (DCIS) who underwent nipple-sparing mastectomy (NSM) with immediate breast reconstruction using silicone implants. Methods We retrospectively analyzed the postoperative complications and oncological safety of 67 breast cancer patients diagnosed with pure DCIS who underwent NSM with immediate breast reconstruction using silicone implants between 2004 and 2018. Results Among the 127 NSM procedures performed, 2 hematomas (1.5%) and 1 partial nipple necrosis (0.7%) were observed. After a mean follow-up of 60months, the local recurrence rate was of 8.9%, the disease-free survival rate was of 90%, and 1 of the patients died. Conclusion Despite the local recurrence rate, we showed that NSM with immediate breast reconstruction using silicone implants is a feasible surgical approach, with a low rate of complications and high survival rates for patients with a diagnosis of pure DCIS when breast-conserving surgery is not an option.